(untitled) (Fiep Bulletin - online, 2014)
The present study of exploratory and descriptive nature has as objective to verify the necessities of the States concerning the AXLE 2 - Human resources and formation, which had subsidized II the National Conference of Sports/2006. For collection of data the Documentary Research (Marconi; Lakatos, 2002), from the set of proposals proceeding from the States. The results of the State Conferences are presented, as well as of the Resolution of II the National Conference of the Sport, approved in the final council of the respective Conference. And, finally it is presented a proposal for formation of the diverse segments that act in the sportive movement and of leisure.